Study on Investment and Private Sector Participation in Power Distribution in Latin America and the Caribbean Region - Herz, Rafael; Kappen, Jan; Monari, Lucio (World Bank, Washington, DC, 2014)
This study presents the results of a survey and analysis of the data available on private participation in the power sector in the period 1990-2002, pointing to a series of preliminary findings, and identifies areas where deeper policy analysis is needed so that modalities for public-private partnerships can be proposed and the sector can again attract the needed investments. The final goal of this desk study is to select two or three countries for further analysis. It would be the objective of a subsequent phase, to analyze case studies and present key lessons learnt in selected countries and compare them with international experience.